Socioeconomic - related inequalities in overweight and obesity: findings from the PERSIAN cohort study - Farid Najafi; Shahin Soltani; Behzad Karami Matin; Ali Kazemi Karyani; Satar Rezaei; Moslem Soofi; Yahya Salimi; Mehdi Moradinazar; Mohammad Hajizadeh; Loghman Barzegar; Yahya Pasdar; Behrooz Hamzeh; et al. (BMC, 2020)
Abstract Background Overweight and obesity are major health concerns worldwide, with adverse health consequences during the life span. This study measured socioeconomic inequality in overweight and obesity among Iranian adults. Methods Data were extracted from 129,257 Iranian adults (aged 35 years and older) participated in the Prospective Epidemiologic Research Studies in IrAN (PERSIAN) in 14 provinces of Iran in 2014. Socioeconomic-related inequality in overweight and obesity was estimated using the Concentration Index (Cn). The Cn further decomposed to find factors explaining the variability within the Socioeconomic related inequality in overweight and obesity. Results Of the total number of participants, 1.98, 26.82, 40.76 and 30.43% had underweight, normal weight, overweight and obesity respectively. The age-and sex standardized prevalence of obesity was higher in females than males (39.85% vs 18.79%). People with high socioeconomic status (SES) had a 39 and 15% higher chance of being overweight and obese than low SES people, respectively. The positive value of Cn suggested a higher concentration of overweight (0.081, 95% confidence interval [CI]; 0.074-0.087) and obesity (0.027, 95% CI; 0.021-0.034) among groups with high SES. There was a wide variation in socioeconomic-related inequality in overweight and obesity rate across 14 provinces. The decomposition results suggested that SES factor itself explained 66.77 and 89.07% of the observed socioeconomic inequalities in overweight and obesity among Iranian adults respectively. Following SES, province of residence, physical activity, using hookah and smoking were the major contributors to the concentration of overweight and obesity among the rich. Conclusions Overall, we found that overweight and obesity is concentrated among high SES people in the study population. . Accordingly, it seems that intersectional actions should be taken to control and prevent overweight and obesity among higher socioeconomic groups.